12x=(x+2)(x+2)

Simple and best practice solution for 12x=(x+2)(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x=(x+2)(x+2) equation:



12x=(x+2)(x+2)
We move all terms to the left:
12x-((x+2)(x+2))=0
We multiply parentheses ..
-((+x^2+2x+2x+4))+12x=0
We calculate terms in parentheses: -((+x^2+2x+2x+4)), so:
(+x^2+2x+2x+4)
We get rid of parentheses
x^2+2x+2x+4
We add all the numbers together, and all the variables
x^2+4x+4
Back to the equation:
-(x^2+4x+4)
We add all the numbers together, and all the variables
12x-(x^2+4x+4)=0
We get rid of parentheses
-x^2+12x-4x-4=0
We add all the numbers together, and all the variables
-1x^2+8x-4=0
a = -1; b = 8; c = -4;
Δ = b2-4ac
Δ = 82-4·(-1)·(-4)
Δ = 48
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{48}=\sqrt{16*3}=\sqrt{16}*\sqrt{3}=4\sqrt{3}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(8)-4\sqrt{3}}{2*-1}=\frac{-8-4\sqrt{3}}{-2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(8)+4\sqrt{3}}{2*-1}=\frac{-8+4\sqrt{3}}{-2} $

See similar equations:

| 4/5(5p–20)+6=10 | | 74=3x+20 | | -4b+7=35 | | 4x2=-6 | | 8x+6x^2=-5x+3x^2 | | .75x=225-x | | 41.8c=133.76 | | C(x)=25x+360 | | 3x2+5x+6+x−1x+2=7x+3x | | 7(x1)=49 | | 13u–3u=10 | | 3(n+3)=24 | | 4x+2x-5=-1 | | 18+1/3k=-8 | | 8x-16=3x | | 6x/4-5=1 | | (3a-4/2)-(2a+5/4)+(3/2)=0 | | 3x+15=3x-17 | | 34=4c-6 | | 54s+36=24s+3 | | C=4.5+0.5m | | 7+17y=58 | | -1(1x-5=9 | | 6(n+3)=24 | | m+42-23=10 | | 160-w=34 | | 6(n+3)=18 | | t=0.6(220-12) | | 46.53/67=x/100 | | 155=5-v | | -7x2-11x-4=0 | | 2x=10=86=x |

Equations solver categories